Diagnostic accuracy of fine needle aspiration cytology in thyroid swellings with histopathological correlation - Patil, Mahadeo R.; M. Patil, Sandhyarani (International Surgery Journal, 2018)
Background: Thyroid swellings are common in India. It is important to differentiate malignant from benign thyroid swellings for definitive planning of appropriate surgery. This study is undertaken to study sensitivity and specificity of FNAC in diagnosis of thyroid swellings by comparing preoperative FNAC with postoperative histopathology. Methods: A total of 156 patients with thyroid swellings were evaluated for a period of three years. Pre-operatively FNAC was done and was compared with post-operative histopathology and sensitivity and specificity of FNAC was studied. Results: Thyroid swellings are more common in females. In present study of 156 thyroid swellings, 90.38% cytologies were benign while 7.05% were malignant and 2.56% were suspicious for malignancy. Sensitivity of FNAC for malignant lesions was 93.75% and specificity was 100%. Conclusions: FNAC with its very high specificity, and diagnostic accuracy approaching 100% can help to rule out malignancy in most of thyroid swellings and prevent unnecessary surgeries.